Effectiveness of Biopesticides Nicotiana tabacum L and Ageratum conyzoides L As Controlling Spodoptera exigua in Red Onion (Allium ascalonicum L.) - Pradinata, Rio; Ginting, Tri Yaninta; Amrul, Hanifa Mutia Z N (Universitas Labuhanbatu, 2024)
Shallots (Allium ascalonicum) are a commodity in Indonesia that has high economic value. One of the pests that often attacks and reduces shallot yields is the onion caterpillar pest S. exigua. Tobacco plants and babadotan weeds are types of plants that can be used as botanical pesticides as a method of controlling and preventing pest attacks on plants. Tobacco and babadotan plants contain secondary metabolite compounds such as alkaloids, flavonoids, saponins, terpenoids and tannins which are able to kill insect pests on shallot plants. The aim of this research is to determine the effectiveness of tobacco extract (Nicotiana tabacum L.) and Babadotan (Ageratum conyzoides L.) as control of the onion caterpillar pest Spodoptera exigua on shallots. The highest combined mortality rate was treated with T6 at 96JSP with an average of 75%,The lowest larval mortality percentage test was found in T2 with an average mortality result of 22.50%.The results of biosafety testing show that the combination of tobacco extract and babadotan extract cannot be used together. From the conclusions that have been obtained, the extracts of (Nicotiana tabacum L.) and (Ageratum conyzoides L.), both single extracts and combination extracts, are effective in controlling the pest S.exigua